2022
DOI: 10.1093/bioinformatics/btac721
|View full text |Cite
|
Sign up to set email alerts
|

ViMRT: a text-mining tool and search engine for automated virus mutation recognition

Abstract: Motivation Virus mutation is one of the most important research issues which plays a critical role in disease progression and has prompted substantial scientific publications. Mutation extraction from published literature has become an increasingly important task, benefiting many downstream applications such as vaccine design and drug usage. However, most existing approaches have low performances in extracting virus mutation due to both lack of precise virus mutation information and their dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, virus mutation is another important factor in escaping the immune protection derived from a previous infection or vaccination [ 14 - 16 ]. Several studies have shown that people living at high altitudes may be less susceptible to developing severe adverse effects from COVID-19, along with reduced case fatality rates [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, virus mutation is another important factor in escaping the immune protection derived from a previous infection or vaccination [ 14 - 16 ]. Several studies have shown that people living at high altitudes may be less susceptible to developing severe adverse effects from COVID-19, along with reduced case fatality rates [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, automatic gathering of mutation effect information may soon become necessary, e.g. , with automatic processes such as ViMRT [42] or crowd-sourcing-based methods such as CoVEffect [43] . However, ViMRT does not classify effects; instead, it extracts phenotype descriptions using regular expression-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent tool called ViMRT [ 35 ] employs ad hoc optimized rules and regular expressions for the extraction of viral mutations; a whole infrastructure is built with this sole purpose, demonstrating the complexity of the task, whose resolution remains largely uncovered.…”
Section: Related Workmentioning
confidence: 99%